Engaging Cinema in Environmental Crisis: A Paradigm of Documentary Films of the Niger Delta - Stephen Ogheneruro Okpadah (Colloquia Humanistica, 2022)
The oil-rich Niger Delta region of Nigeria remains one of the most environmentally devastated places in the world. This is caused by gas flaring, crude oil spillages, illegal oil bunkering and pipeline vandalism in the region. The call for eco-democracy and the disruption of eco-apathy has driven global academia into developing paradigms that would foster environmental transformation. Interestingly, while academic disciplines such as history, geography, anthropology and the global humanities continue to critically engage in practices and discourses that would facilitate achieving anticipatory climate adaptation, African academia, especially in Nigeria, has been slow to absorb the same critical spirit as the West. In fact, environmental film critics in Nigeria have not fully explored the environmental discourse that has gathered strength in other disciplines central to the greening of the humanities. Therefore, there remains a dearth of critical underpinning for environment and cinema, or what I term discourses of/on the green cinema, in African scholarship. Against this backdrop, I examine environmental crisis in the documentary films Delta Blues, The Nigerian Oil Thieves and The True Price of Crude Oil, and use content analysis method to investigate how these films have been used to create environmental awareness in the region. The analysis is anchored on Adrian Ivakhiv’s biocentric model of ecocriticism, which acknowledges the unity of man and all the creatures and the environment around him, and further recommends a shift from human-centrism to biocentrism.